2013
DOI: 10.1080/19443994.2013.826851
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing the rejection of trace organic contaminants by nanofiltration and reverse osmosis membranes

Abstract: A B S T R A C TThis study aimed to elucidate key factors governing the rejection of trace organic contaminants (TrOCs) by nanofiltration (NF) and reverse osmosis (RO) membranes. The rejection of 16 selected hydrophilic and hydrophobic TrOCs by an NF and an RO membranes was evaluated at different solution pH values using a cross-flow NF/RO filtration system. An analytical technique consisting of solid phase extraction followed by gas chromatography and mass spectrometry detection was used for the analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Furthermore, a number of studies have also shown that NF and ultralow pressure RO membranes are not perfect barriers for various micropollutants including endocrine disruptors and some PhACs such as SMX or CBZ [15,16]. Both membranes had a negative surface charge in the pH range used in the study [17,18], whereas the hydrophobic nature of a membrane is typically characterised by its contact angle. Alturki et al [7] measured the contact angle of both the NF90 and ESPA2 membranes for virgin membranes (1 hour use) and after 25 hours of use.…”
Section: -Acetylsulfapyridine (Acspy) Demonstrated That the Marine Bmentioning
confidence: 99%
“…Furthermore, a number of studies have also shown that NF and ultralow pressure RO membranes are not perfect barriers for various micropollutants including endocrine disruptors and some PhACs such as SMX or CBZ [15,16]. Both membranes had a negative surface charge in the pH range used in the study [17,18], whereas the hydrophobic nature of a membrane is typically characterised by its contact angle. Alturki et al [7] measured the contact angle of both the NF90 and ESPA2 membranes for virgin membranes (1 hour use) and after 25 hours of use.…”
Section: -Acetylsulfapyridine (Acspy) Demonstrated That the Marine Bmentioning
confidence: 99%
“…Micropollutant concentration in the enzymatic bioreactor and membrane permeate was measured by High-performance liquid chromatography (HPLC) (Shimadzu, Kyoto, Japan) at the detection wavelength of 280 nm using a method reported previously (Nguyen et al, 2014b [8,40], [10,0], [22,0], [24,85]. The gradient of eluent B was then automatically adjusted as follows: [Time (min), B (%)]: [0, 15], [8,60], [10,100], [22,100], [24,15]. The limit of detection (LOD) for this method was approximately 10 µg/L.…”
Section: Methodsmentioning
confidence: 99%
“…Overall removal of micropollutantsIn this study, NF-EMBR achieved 92 to over 99% removal of the micropollutants(Figure 2). In general, NF membranes can remove micropollutants via the following mechanisms: (i) size exclusion; (ii) adsorption; and (iii) electrostatic interaction(Dang et al, 2014;Taheran et al, 2016). Micropollutants having a molecular weight higher than 200 g/mol have been reported to be effectively rejected by the NF90 membrane(Luo et al, 2014a).…”
mentioning
confidence: 99%
“…Most of them are carried out in developed countries . Improvements in wastewater treatment field and the search for new treatment methods have been carried out, such as ozonation and osmosis, in order to effectively remove organic contaminants (PISARENKO et al, 2012;SHEN et al, 2014;DANG, NGHIEM and PRICE, 2014).…”
Section: *Sd = Standard Deviationmentioning
confidence: 99%